2018
DOI: 10.1016/j.yebeh.2018.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Long-term monotherapy treatment with vitamin E reduces oxidative stress, but not seizure frequency in rats submitted to the pilocarpine model of epilepsy

Abstract: The imbalance between antioxidant system and reactive oxygen species (ROS) generation is related to epileptogenesis, neuronal death, and seizure frequency. Treatment with vitamin E has been associated with neuroprotection and control of seizures. In most experimental studies, vitamin E treatment has short duration. Therefore, the aim of this study was to verify the role of long-term treatment with vitamin E in rats submitted to the pilocarpine model of epilepsy. Rats were divided into two main groups: control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…This was confirmed in a recent study, which demonstrated that long-term treatment with 60 IU/kg/day of vitamin E prevented oxidative damage in the hippocampus and increased hilar parvalbumin expression in rats with epilepsy without a reduction in seizure frequency [53].…”
Section: Neuroprotective and Antiepileptogenic Role Of Ros Inhibitionsupporting
confidence: 69%
“…This was confirmed in a recent study, which demonstrated that long-term treatment with 60 IU/kg/day of vitamin E prevented oxidative damage in the hippocampus and increased hilar parvalbumin expression in rats with epilepsy without a reduction in seizure frequency [53].…”
Section: Neuroprotective and Antiepileptogenic Role Of Ros Inhibitionsupporting
confidence: 69%
“…There have been reports of the successful use of antioxidants, such as α‐tocopherol/vitamin E in status epilepticus, reducing neuronal injury and inflammation. 34 , 35 , 36 However, many of the studies of antioxidants have mixed results and are confounded by timing of administration, blood‐brain barrier penetration, doses used, and coadministration with other compounds. 37 In addition, the translational potential of many of the studies is low, as the antioxidant is given prior to the induction of status epilepticus.…”
Section: Neuroprotective Role Of Antioxidant Strategiesmentioning
confidence: 99%
“…The observations that free radical generation occurs during status epilepticus and that there are key roles of peroxynitrite and ROS in mitochondrial dysfunction and neuronal death (Figure 1) lead to the supposition that antioxidants should have a neuroprotective effect. There have been reports of the successful use of antioxidants, such as α‐tocopherol/vitamin E in status epilepticus, reducing neuronal injury and inflammation 34–36 . However, many of the studies of antioxidants have mixed results and are confounded by timing of administration, blood‐brain barrier penetration, doses used, and coadministration with other compounds 37 .…”
Section: Neuroprotective Role Of Antioxidant Strategiesmentioning
confidence: 99%
“…In some of these studies, the anticonvulsant action of vitamin E was accompanied by a lowering of brain lipid peroxidation and nitrite content, which may result in increased cytoprotection and neuronal survival as ultimate prevention mechanisms against hippocampal damage [23]. Other recent studies on pilocarpine-induced epilepsy model have confirmed the protection against oxidant stress of the brain, but not the anticonvulsant activity [154], pointing to different levels of outcome for different dosages of the vitamin and epileptogenic models.…”
Section: Vitamin E: An Effective Fighter In Counteracting Oxidative S...mentioning
confidence: 99%